Ambient noise and neonatal hemodynamics - An observational cross-sectional study - Karambelkar, Geeta R; Malwade, Sudhir D; Kewalramani, Disha; Agarkhedkar, Sharad R; Chalipat, Shiji S (Indian Journal of Child Health, 2018)
Background: Previous studies reported numerous adverse effects of noise in the newborns such as increase in the heart rate (HR) and respiratory frequency and drop in the oxygen saturation. Objective: The objective of this study was to study the effect of ambient noise levels in neonatal intensive care unit (NICU) on the hemodynamics of neonates. Materials and Methods: This was a hospital-based cross-sectional observational study which aimed at assessing the ambient noise levels in the NICU with a digital decibel meter and its effect on HR, respiratory rate (RR), and oxygen saturation. A total of 105 neonates (both preterm and term) having stable cardiorespiratory status were enrolled in the study. Results: The mean noise level recorded in the NICU was 56.2 dB. The lowest noise level was recorded at 8 am, that is, 46 dB while the highest recorded level was at 2 pm, that is, 65 dB in different areas of the NICU. There was a statistically significant increase in the HR in relation to the noise levels at all times (p